IOT based Advanced Medicine Dispenser Integrated with an Interactive Web Application - Kishor Panda, Nanda; Bhardwaj, Shubham; Bharadwaj, H.; Singhvi, Rohil (International Journal of Engineering and Technology, 2018)
Internet of Things (IOT) is a development of the internet which plays aÂ  major role in integrating human-machine interaction by allowing everyday objects to send and receive data in a variety of applications. Using IOT in healthcare monitoring provides an avenue for doctors and patients to interact and to track the dosage of medication administered. The paper presents an interactive, user friendly network integrated with an automated medicine dispenser which uses IOT, cloud computing and machine learning. The network was built on a python tornado framework with a front end developed using materialise CSS. The feasibility of this approach was validated by building a prototype and conducting a survey.Â Â